Sinapic Acid Reduces Oxidative Stress and Pyroptosis via Inhibition of BRD4 in Alcoholic Liver Disease - Chu, Junyi; Yan, Ran; Wang, Sai; Li, Guoyang; Kang, Xiaohui; Hu, Yan; Lin, Musen; Shan, Wen; Zhao, Yan; Wang, Zhecheng; Sun, Ruimin; Yao, Jihong; et al. (Frontiers in Pharmacology, 2021)
Alcoholic liver disease (ALD) is one of the main causes of death in chronic liver disease. Oxidative stress and pyroptosis are important factors leading to ALD. Bromodomain-containing protein 4 (BRD4) is a factor that we have confirmed to regulate ALD. As a phenolic acid compound, sinapic acid (SA) has significant effects in antioxidant, anti-inflammatory and liver protection. In this study, we explored whether SA regulates oxidative stress and pyroptosis through BRD4 to play a protective effect in ALD. Male C57BL/6 mice and AML-12 cells were used for experiments. We found that SA treatment largely abolished the up-regulation of BRD4 and key proteins of the canonical pyroptosis signalling in the liver of mice fed with alcohol, while conversely enhanced the antioxidant response. Consistantly, both SA pretreatment and BRD4 knockdown inhibited oxidative stress, pyroptosis, and liver cell damage in vitro. More importantly, the expression levels of BRD4 and pyroptosis indicators increased significantly in ALD patients. Molecule docking analysis revealed a potent binding of SA with BRD4. In conclusion, this study demonstrates that SA reduces ALD through BRD4, which is a valuable lead compound that prevents the ALD process.